The Impact of the Imtaq Program Activities on the Development of Students' Spiritual Potential at State High School 1 Pajar Bulan - Wulan Sari; Fita Sarpika (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The goal of this research is to determine the effect of the Imtaq program activities on the development of students' spiritual potential at State High School 1 Pajar Bulan. It also aims to identify the supporting and inhibiting factors. Methodology: The research methodology used is a type of research (field research) with a quantitative approach. The population in this study consists of 243 people and the sample is 60 people, using stratified random sampling technique. Data collection was conducted through observation, questionnaires, interviews, and documentation. The data were analyzed using simple linear regression testing. Main Findings: A significance value of 0.000 was obtained, which is smaller than 0.05 (0.000<0.05), indicating that Ha is accepted and Ho is rejected, meaning that the Imtaq program has a positive and significant influence on the development of the spiritual potential of students at State High School 1 Pajar Bulan. The contribution of the Imtaq program to the development of spiritual potential in this study is 95.6%, while 4.4% is influenced by other factors. The Imtaq program is supported by all teachers and staff as well as adequate facilities, while the inhibiting factors are the lack of motivation and role modeling from parents at home as well as the students' low ability to read the Qur'an. Novelty/Originality of this study: It emphasizes the in-depth aspects of students' character, including religious principles, direction in life, identity, and noble ethics. Furthermore, it not only focuses on the outcomes or implications but also provides space to assess the form and quality of IMTAQ activities implemented in educational institutions. This makes the study significant for other public schools as a step to strengthen character education based on spiritual values.